Living Donor Liver Transplantation for Acute Liver Failure: Donor Safety and Recipient Outcome. Issue 9 (29th July 2019) - Pamecha, Viniyendra; Vagadiya, Ankur; Sinha, Piyush Kumar; Sandhyav, Rommel; Parthasarathy, Kumaraswamy; Sasturkar, Shridhar; Mohapatra, Nihar; Choudhury, Ashok; Maiwal, Rakhi; Khanna, Rajeev; Alam, Seema; Pandey, Chandra Kant; et al.
Abstract : In countries where deceased organ donation is sparse, emergency living donor liver transplantation (LDLT) is the only lifesaving option in select patients with acute liver failure (ALF). The aim of the current study is living liver donor safety and recipient outcomes following LDLT for ALF. A total of 410 patients underwent LDLT between March 2011 and February 2018, out of which 61 (14.9%) were for ALF. All satisfied the King's College criteria (KCC). Median admission to transplant time was 48 hours (range, 24‐80.5 hours), and median living donor evaluation time was 18 hours (14‐20 hours). Median Model for End‐Stage Liver Disease score was 37 (32‐40) with more than two‐thirds having grade 3 or 4 encephalopathy and 70% being on mechanical ventilation. The most common etiology was viral (37%). Median jaundice‐to‐encephalopathy time was 15 (9‐29) days. Preoperative culture was positive in 47.5%. There was no difference in the complication rate among emergency and elective living liver donors (13.1% versus 21.2%; P = 0.19). There was no donor mortality. For patients who met the KCC but did not undergo LT, survival was 22.8% (29/127). The 5‐year post‐LT actuarial survival was 65.57% with a median follow‐up of 35 months. On multivariate analysis, postoperative worsening of cerebral edema (CE; hazard ratio [HR], 2.53; 95% confidence interval [CI], 1.01‐6.31), systemic inflammatory response syndrome (SIRS; HR, 16.7; 95% CI, 2.05‐136.7), preoperative culture positivity (HR, 6.54; 95% CI, 2.24‐19.07), and a longer anhepatic phase duration (HR, 1.01; 95% CI, 1.00‐1.02) predicted poor outcomes. In conclusion, emergency LDLT is lifesaving in selected patients with ALF. Outcomes of emergency living liver donation were comparable to that of elective donors. Postoperative worsening of CE, preoperative SIRS, and sepsis predicted outcome after LDLT for ALF.